My dog is better than your dog - Greenwald, Tom, 1962- (Greenwald, Tom, 1962- Crime biters!, 2015)
Jimmy Bishop likes crime fighters, vampires, and dogs, and he does not care for his new babysitter, so he is delighted when his new dog, Abby--who sleeps during the day, and grows huge fangs at night--turns out to be a crime-fighting, vampire dog, who also does not like the babysitter.